Beneficial Effect Of Zink Spraying On Growth and Yield Safflower Plants (Carthamus tinctorius L.) - ABD ELAziz, Mohamed; Yousef, Sewar (Latakia University Journal -Biological Sciences Series, 2019)
The research was carried out during 2016 and 2017 seasons to study the effect of znso4 spraying safflower plants , using following treatments. 1-Control without spraying or fertilization (T1). 2- Mineral fertilization (T2). 3- Mineral fertilization + Zn spraying at 0.50% (T3). 4- Mineral fertilization + Zn spraying at 1.0% (T4). 5- Mineral fertilization + Zn spraying at 1.5% (T5). Treatments were arranged in a complete randomized black design with three replications. The results showed that: The spraying with all studies concentration (0.5 , 1.0, 1.5) % in begining and flowering stages caused significantly increase plant height , branches , Leaves , heads/ plant, seed yield/plant and seed yield / ha compared to the control (T1) and the meniral fertilization (T2). The spraying with 1% concentration (T4) significant increased on 0.5% and 1.5% concentration at leaves number 72.77 /plant , seeds yield 44.74 g/plant and seed yield 2422kg / ha during the two seasons. There were not significantly increase at all studies parameters between the first and second seasons. The interaction between treatments and seasons (T4 x first seasons), there were significant increase and big higher value 89. 92 cm in plant height , 13.12 branches , 38.69 heads , 83.12 leaves numbers/plant , 45.21g seed yield / plant and 2464 kg/ha seeds yield, expect of leaf area 2427 cm2 it was per the interaction between (T5 x second seasons) نفذ البحث خلال الموسمين 2016 و 2017 لدراسة تأثير رش الزنك على نبات العصفر واستخدم لذلك أربعة معاملات هي: 1-شاهد بدون رش أو تسميد (T1) 2-معاملة التسميد المعدني فقط (T2) 3-معاملة التسميد المعدني + رش الزنك بالتركيز 0.5% (T3) 4-معاملة التسميد المعدني+ رش الزنك بتركيز (T4) % 1 5- معاملة التسميد المعدني + رش الزنك بتركيز (T5)% 1.5 في بعض صفات النمو والغلة لنبات العصفر. صممت التجربة بالطريقة العشوائية الشاملة في ثلاث مكررات. بينت الدراسة النتائج الآتية: أدى رش الزنك بالتراكيز المدروسة في بداية مرحلة التفرع , وبداية مرحلة الإزهار إلى تفوق كافة المعاملات في ارتفاع الساق(سم) وعدد الفروع /النبات/, وعدد النورات /النبات/, وعدد الأوراق /النبات/ والمسطح الورقي سم2/ النبات , وغلة البذور غ/النبات ، وغلة الهكتار من البذور مقارنة مع الشاهد (T1),ومع معاملة التسميد المعدني (T2). تفوق تركيز الرش 1%(T4) معنويا على التركيزين 0.5% و 1.5% في عدد الأوراق 82.37 ورقة/النبات، وإنتاجية النبات 44.74 غ وإنتاجية البذور 2422 كغ/ه خلال موسمي البحث. لم يوجد للموسم الزراعي تأثيراً معنوياً في جميع الصفات المذكورة أعلاه, وكانت الفروقات ظاهرية وغير معنوية عند المستوى 5%. وجدت أكبر قيم للتفاعل بين المعاملة (T4 X الموسم الثاني) في ارتفاع الساق 89.92 سم, وعدد الفروع 13.12, وعدد النورات 38.69, وعدد الأوراق 83.12, وإنتاجية النبات 45.21 غ , وإنتاجية البذور 2464 كغ/ه باستثناء المسطح الورقي2427 سم2 للتفاعل بين(T5 Xالموسم الثاني).